Gluteal flap for omphalocele repair in a case of epigastric heteropagus: A novel approach for surgical management - Krushnakumar Kesan; Abhaya Gupta; Rahul Kumar Gupta; Paras Kothari; Ritesh Ranjan; Parag Karkera; Kedar Mudkhedkar (Indian Journal of Plastic Surgery)
Epigastric heteropagus is an extremely rare congenital anomaly, in which there is asymmetrical conjoined twinning, with the parasitic twin attached to the epigastrium. A 2-day-old male, with epigastric heteropagus and omphalocele, was operated in our institution. After excision of the parasitic twin, omphalocele was covered with a gluteal skin flap available from the parasitic twin. Post-operative course was uneventful, except for infection along the edges of the skin flaps, which was managed conservatively. Only 44 cases of epigastric heteropagus twins have been reported previously in world literature. We present a novel surgical approach for the repair of the omphalocele in a case of epigastric heteropagus twins, probably the 45 th case to be reported in the world literature.